The Seamless Integration of Wearables with EHR Systems: An AI-Driven Path to Predictive Healthcare - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The healthcare landscape is shifting from an episodic, reactive model to one of continuous, proactive monitoring, driven by the proliferation of consumer and...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Medical Ethics; Clinical Decision Support